Diagnostic of Leucoptera coffeella (Lepidoptera: Lyonetiidae) and its parasitoids in the department of Antioquia, Colombia - David-Rueda, Gonzalo; Constantino C., Luis Miguel; Montoya, Esther Cecilia; Ortega M., Oscar E.; Gil, Zulma Nancy; Benavides-Machado, Pablo (Revista Colombiana de Entomología, 2016)
Coffee Leaf Miner, Leucoptera coffeella is one of the main insect coffee pests in the Neotropics, causing yield decreases up to 80%, in countries such as Brazil. In Colombia, this insect pest has been poorly studied, since the damage it causes has been sporadic. This exploratory investigation was carried out in order to diagnose the damage caused by the coffee leaf miner and its parasitoids in the department of Antioquia. Pest infestation levels were evaluated as to incidences of natural parasitism, identifying the species of the parasitoids, through a bietapic sampling performed in more than 1,100 coffee crops between the ages of 2 and 5 years. Sixty (60) coffee trees per crop were evaluated four times through systematic sampling between 2013 and 2014. The results indicated an average of leaf miner infestation level under 2%, and parasitism levels between 58 and 89 %. In total, 787 parasitoid individuals emerged, all belonged to the Order Hymenoptera, family Eulophidae, comprising two subfamilies: Eulophinae and Entodininae. Seven parasitoid species were identified: Closterocerus coffeellae, Closterocerus lividus, Zagrammosoma multilineatum, Pnigalio sarasolai, Horismenus sp., Horismenus n. sp., and Apleurotropis n. sp. These last two new species for Colombia, and perhaps for science. The most abundant natural enemy of coffee leaf miner was the species C. coffeellae. The management of this insect pest by means of a conservation biological control strategy is recommended.